2020
DOI: 10.1017/s1368980020001135
|View full text |Cite
|
Sign up to set email alerts
|

Geospatial analysis of Mediterranean diet adherence in the United States

Abstract: Objective: The current study aims to describe the Mediterranean diet (MD) adherence across the US regions, and explore the predictive factors of MD adherence among US adults. Design: Cross-sectional secondary data analysis. MD adherence score (0–9) was calculated using the Block 98 FFQ. Hot spot analysis was conducted to describe the geospatial distribution of MD adherence across the US regions. Logistic regression explored predictors of MD adherence. Setting: Nationwid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…In agreement with previous versions, the 2020–2025 version of the Dietary Guidelines for Americans [ 11 ] currently includes the Healthy Mediterranean-Style Dietary Pattern, which is considered a variation of the Healthy US-Style Dietary Pattern, based on the types and proportions of foods typically consumed by Americans, although in nutrient-dense forms and appropriate amounts. A very recent study conducted a geospatial analysis of Mediterranean diet adherence (assessed by the MD adherence score) in the US [ 54 ], collecting data across the US regions and exploring the predictive factors of such adherence among US adults (over 20,000 participants). High adherence was observed in 46.5% of the sample.…”
Section: Adherence To the Mediterranean Diet And Geographic Location ...mentioning
confidence: 99%
“…In agreement with previous versions, the 2020–2025 version of the Dietary Guidelines for Americans [ 11 ] currently includes the Healthy Mediterranean-Style Dietary Pattern, which is considered a variation of the Healthy US-Style Dietary Pattern, based on the types and proportions of foods typically consumed by Americans, although in nutrient-dense forms and appropriate amounts. A very recent study conducted a geospatial analysis of Mediterranean diet adherence (assessed by the MD adherence score) in the US [ 54 ], collecting data across the US regions and exploring the predictive factors of such adherence among US adults (over 20,000 participants). High adherence was observed in 46.5% of the sample.…”
Section: Adherence To the Mediterranean Diet And Geographic Location ...mentioning
confidence: 99%
“…The top 25% of scorers in the current study had a mean score of 16.45 (out of 100). Direct comparison to the Chen et al ( 11 ) study proves problematic given the significant differences in study methodologies. For example, data were assessed in the Chen et al ( 11 ) study using an MSDP scoring system that did not mention accounting for overconsumption of “detrimental” foods (i.e., added sugars).…”
Section: Discussionmentioning
confidence: 94%
“…Unlike the nationally representative sample used in the current study, the Framingham Heart Study is based in the northeastern region of the United States. Chen et al ( 11 ) found that 46.5% of their study participants had high adherence (scoring from 5–9 out of 9 points) using an FFQ among 20,897 Americans. The top 25% of scorers in the current study had a mean score of 16.45 (out of 100).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In a population aged ≥ 85, education played the most important role among many factors, such as sex, BMI, disease history, cognitive function, and marital status, with differences in DPs [ 31 ]. In addition, some individuals face challenges, including geographic information of residence, access to foods and locations to engage in PA, ethnic-specific cultural values and dietary habits, and commercial influences [ 30 , 31 , 32 , 33 ]. Nevertheless, the trend toward a healthier diet has been positively associated with PA in different countries and ages.…”
Section: Discussionmentioning
confidence: 99%